2022
DOI: 10.3390/ijerph19074413
|View full text |Cite
|
Sign up to set email alerts
|

Resilience-Building for Mental Health among Early Childhood Educators: A Systematic Review and Pilot-Study towards an EEG-VR Resilience Building Intervention

Abstract: Resilience is a key factor that reflects a teacher’s ability to utilize their emotional resources and working skills to provide high-quality teaching to children. Resilience-building interventions aim to promote positive psychological functioning and well-being. However, there is lack of evidence on whether these interventions improve the well-being or mental health of teachers in early childhood education (ECE) settings. This review examined the overall effectiveness of resilience-building interventions condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Gratitude interventions for depression and anxiety may be minimally helpful (Cregg & Cheavens, 2021). Further, resilience programs for ECEs have mixed results (Abu Hasan et al, 2022) and some may unintentionally cause more stress (Lang et al, 2020). This may be because, given the need to manage multiple stressors while financially strapped, ECEs are already resilient.…”
Section: Implications For the Practitioner In The Schoolsmentioning
confidence: 99%
“…Gratitude interventions for depression and anxiety may be minimally helpful (Cregg & Cheavens, 2021). Further, resilience programs for ECEs have mixed results (Abu Hasan et al, 2022) and some may unintentionally cause more stress (Lang et al, 2020). This may be because, given the need to manage multiple stressors while financially strapped, ECEs are already resilient.…”
Section: Implications For the Practitioner In The Schoolsmentioning
confidence: 99%
“…Resilient individuals utilize positive emotions to bounce back from negative emotional experiences, as proposed by (Tugade & Fredrickson, 2004). These interventions aim to promote positive psychological functioning and well-being, particularly in the face of stress and adversity (Hasan et al, 2022). For instance, psychological resilience-building interventions have been found to be effective in promoting resilience and reducing depression, anxiety, and stress among healthcare workers during the COVID-19 pandemic (Wu et al, 2022).…”
Section: Psychological Approaches To Building Resiliencementioning
confidence: 99%
“…As it is an immensely growing field, therefore, administrators highly need to pay the attention to its corresponding policies, being more concerted to the wellbeing of teachers. During the COVID-19 pandemic, (Abu Hasan et al, 2022 ) reported on the rising number of instructors being employed in public and private institutes at all levels, and how the stress rate during lockdown was dangerously high among those teachers, at 89 percent. With such a large workforce in the department, it must be handled immediately by guaranteeing the best possible use of technology to avoid more economic disasters.…”
Section: Introductionmentioning
confidence: 99%